Selection objectives and criteria for sheep in Central Brazil - Pimentel, Concepta Margaret McManus (2011)
Three production systems for sheep (Low - L, Medium - M and High - H technology), with increasing technological levels, were studied under conditions in the Center-west of Brazil, to determine economic weights and selection indices of important traits. Receipts and costs were simulated using an economic simulator to calculate the structure of the operational costs. Only characteristics that were responsible for more than 10% of the profit were studied, which included: number of weaned lambs, food consumption (ewe and lamb), weight of carcass and weight of female lambs sold for reproduction. Regardless of the index used (profitability or yield) or system (L, M or H), the economic weights are larger for the number of lambs weaned per ewe. With improvement in the technology used within the production system (H to L) the importance of this trait becomes less important. Lamb growth increased and weight of female for slaughter decreased in importance in higher technology systems. Changes in herd structure had little influence on economic values, whereas (co)variances were important sources of change in selection indices.